Superpixel-based segmentation algorithm for mature citrus - Yang, Qinghua; Chen, Yiqin; Xun, Yi; Bao, Guanjun (International Journal of Agricultural and Biological Engineering, 2020)
With the decrease of agricultural labors and the increase in production costs, harvesting robots have become a research hotspot in recent years. To guide harvesting robots to pick mature citrus more precisely under variable illumination conditions, an image segmentation algorithm based on superpixel was proposed. Efficient simple linear iterative clustering (SLIC) algorithm which takes similarity of adjacent pixels into account was adopted to segment the images captured under variable illumination conditions into superpixels. The color and texture features of these superpixels were extracted and fused into feature vectors as descriptors to train backpropagation neural networks (BPNN) classifier in the next step. The adjacency information of superpixels was considered by calculating the global-local binary pattern (LBP) in R component images when extracting texture features. To accelerate the classification process, the mean of Cr-Cb image was utilized to find superpixels of interest which were regarded as candidates of citrus superpixels. These candidates were then classified by a pre-trained BPNN model with superpixel-level accuracy of 98.77% and pixel-level accuracy of 94.96%, while the average time to segment one image was 0.4778 s. Therefore, the results indicated that a superpixel-based segmentation algorithm toward citrus images had decent light robustness as well as high accuracy that could guide harvesting robot to pick mature citrus efficiently.Keywords: superpixel, image segmentation, BPNN, variable illumination, mature citrusDOI: 10.25165/j.ijabe.20201304.5607Citation: Yang Q H, Chen Y Q, Xun Y, Bao G J. Superpixel-based segmentation algorithm for mature citrus. Int J Agric & Biol Eng, 2020; 13(4): 166–171.